The presence of diabetes mellitus further impairs structural and functional capillary density in patients with chronic kidney disease. (30th October 2020) - Schoina, Maria; Loutradis, Charalampos; Theodorakopoulou, Marieta; Dimitroulas, Theodoros; Triantafillidou, Eva; Doumas, Michael; Karagiannis, Asterios; Garyfallos, Alexandros; Papagianni, Aikaterini; Sarafidis, Pantelis
Abstract: Objective: Endothelial dysfunction has been associated with increased cardiovascular events and overall mortality. Microvascular damage is prevalent both in diabetes mellitus (DM) and chronic kidney disease (CKD). Our aim was to compare microcirculatory function parameters in diabetic and non‐diabetic CKD patients via nailfold video‐capillaroscopy. Methods: We included 48 diabetic and 48 non‐diabetic adult CKD patients. All participants underwent nailfold video‐capillaroscopy, during which capillary density was measured at normal conditions (baseline), after a 4‐minute arterial occlusion (postocclusive reactive hyperemia), and at the end of a 2‐minute venous occlusion (congestion phase). Results: Diabetic patients presented significantly lower capillary density during reactive hyperemia (36.3 ± 3.8 vs 38.3 ± 4.3 capillaries/mm 2, P  = .022) and at venous congestion (37.8 ± 4.0 vs 39.8 ± 4.2 capillaries/mm 2, P  = .015). When stratified according to CKD stages, only in stage 3b capillary density was significantly lower in diabetic compared to non‐diabetic subjects at baseline, during postocclusive hyperemia (36.8 ± 2.7 vs 40.0 ± 4.3 capillaries/mm 2, P  = .037) and venous congestion (38.3 ± 2.8 vs 41.5 ± 3.5 capillaries/mm 2, P  = .022). Conclusions: Capillary density during postocclusive hyperemia and after venous congestion is lower in diabetic compared to non‐diabetic CKD patients, a finding indicative that diabetes is an additional factor contributing to microcirculatory structural and functional impairment in CKD. These differences are more prominent in CKD stage 3b.